Improving Medication Safety Through Medication Reconciliation in Pediatric Neurology: Clinical Pharmacist Recommendations and Physician Uptake in a 13-Week Study - Margherita Zennaro; Anna Trotter; Daniele Mengato; Laura Camuffo; Claudio Ancona; Irene Toldo; Maria Cecilia Giron; Maria Federica Pelizza; Margherita Nosadini; Giorgio Perilongo; Stefano Sartori; Francesca Venturini (Children)
Background/Objectives: Clinical pharmacy plays a crucial role in optimizing medication use, particularly in pediatric settings where drug therapy can be complex and understudied. This study aims to assess the impact of clinical pharmacists in the Pediatric Neurology and Neurophysiology Unit of the Padova University Hospital, focusing on physician acceptance of pharmacist suggestions and the types of advice most frequently followed. Methods: A retrospective observational study was conducted over 13 weeks to describe the implementation phase of clinical pharmacists’ involvement in medication reconciliation in this setting. The study consisted of three steps. The study utilized a cluster model to categorize pharmacist suggestions and to evaluate physician acceptance rates. Results: The study included 57 hospitalized pediatric patients (53% male) with a median age of 3 years (IQR: 1–10.25). A total of 138 recommendations were shared, with an overall acceptance rate of 42%. Medication errors accounted for the largest cluster of suggestions (45%), though only 32% were accepted. Among the most frequently shared categories of suggestions, pharmaceutical form optimization (A) and drug supply (E) exhibited higher acceptance rates by clinicians (64% and 42%, respectively). The acceptance rate increased over time, peaking at 100% during weeks 7 and 11, correlating positively with enhanced collaboration between pharmacists and clinicians (R2 = 0.59). Conclusions: This study highlights the importance of clinical pharmacists in pediatric care, particularly in improving medication management through targeted interventions. The findings suggest that integrating clinical pharmacists into multidisciplinary teams can enhance patient care quality by fostering collaboration and trust among healthcare professionals.